Matched trauma: The role of parents' and children's shared history of childhood domestic violence exposure in parents' report of children's trauma-related symptomatology. Issue 1 (1st January 2016) - Cohodes, Emily; Hagan, Melissa; Narayan, Angela; Lieberman, Alicia
ABSTRACT: Parents' childhood experiences of trauma may influence their reports of their children's behavior, and this may be particularly true when children are also traumatized. The present study proposed and tested a matched trauma hypothesis, positing that compared to parents without a childhood history of witnessing domestic violence (DV), parents with a childhood history of witnessing DV may report their children's trauma-related symptomatology differently following children's exposure to DV. Of 137 included parents ( M  age = 32 years; 93% mothers), 81 reported witnessing childhood DV (matched group), whereas 56 reported no childhood DV exposure (nonmatched comparison group). All parents reported on their 3- to 6-year-old children's dissociation and posttraumatic stress symptoms following children's DV exposure. An analysis of covariance controlling for parental life stress, dissociation symptoms, and other childhood traumatic events revealed that parents who witnessed childhood DV reported significantly fewer child dissociation symptoms than comparison parents. No difference was found for parents' reports of children's posttraumatic stress symptoms. Exploratory analyses on a subsample of children with teacher reports of child dissociation symptoms ( n  = 75) revealed that the strength of the association between parent and teacher reports of dissociation symptoms was moderated by matched versus nonmatched group membership. Findings suggest the importance of considering a parent's history of trauma when using parents as informants for children's trauma symptoms.